Making the new Middle East politics, culture, and human rights - Hoffman, Valerie J. 1954- (Syracuse, New York Syracuse University Press, 2019)
Religion, politics, and society in the Middle East -- Religion and politics in the Arab Spring and its aftermath / Valerie J. Hoffman -- The Islamic Republic and the politics of the new Middle East / Behrooz Ghamari-Tabrizi -- The military, the Islamists, and the battle over Egypt's constitution / Feisal G. Mohamed -- Old and new battles for Turkish national identity / Joshua D. Hendrick -- Security challenges in Tunisia, Libya, Morocco, and Algeria in the wake of the Arab uprisings / Ramazan Erda -- Human rights in the Middle East -- Islam, non-Muslim minorities, and human rights in the Middle East / Valerie J. Hoffman -- Regime ruptures and sectarian eruptions in post-Mubarak Egypt / Mariz Tadros -- The Palestinians : justice denied / Cheryl A. Rubenberg -- Gender dynamics : what has changed? -- Gender norms in the Muslim Middle East / Valerie J. Hoffman -- The politics of gender equality in Turkey / Gül Aldıkaçtı Marshall -- Between a rock and a hard place : the "Arab Spring," women, and lessons from Iran / Haideh Moghissi -- Media and cultural expressions -- State-sponsored media, cultural production, and information wars : the case of Iran / Niki Akhavan -- The power of corruption and the corruption of power : the Arabic historical novel in Morocco (and elsewhere) / Roger Allen -- From Sayed Darwish to MC Sadat : sonic cartographies of the Egyptian uprising / Ted Swedenburg
This book examines politics and social dynamics in the Middle East today from diverse disciplinary perspectives, including religion, economics, gender, human rights, literature, media and music
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Women -- Middle East -- Social conditions -- 21st century; Mass Media -- Middle East -- History -- 21st century; Religion And Politics -- Middle East -- History -- 21st century; Wandel; Politischer Wandel; Soziokultureller Wandel; Gesellschaft; Entwicklung; Situation; Aktualität; Politik; Religion; Menschenrecht; Geschlechterrolle; Kultur; POLITICAL SCIENCE ; World ; Middle Eastern; Civilization; Mass Media; Politics and government; Religion And Politics; Women ; Social conditions; HISTORY ; Middle East ; General; History; Middle East -- Politics and government -- 21st century; Middle East -- Civilization -- 21st century; Naher Osten; Mittlerer Osten; Nordafrika; Middle East; Electronic books; Aufsatzsammlung